2016
DOI: 10.1039/c5fo01228g
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protocatechuic acid ameliorates dextran sulphate sodium-induced ulcerative colitis and hepatotoxicity in rats

Abstract: The present study investigated the antioxidant and anti-inflammatory effects of dietary protocatechuic acid (PCA), a simple hydrophilic phenolic compound commonly found in many edible vegetables, on dextran sulphate sodium (DSS)-induced ulcerative colitis and its associated hepatotoxicity in rats. PCA was administered orally at 10 mg kg(-1) to dextran sulphate sodium exposed rats for five days. The result revealed that administration of PCA significantly (p < 0.05) prevented the incidence of diarrhea and bleed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 43 publications
10
36
1
Order By: Relevance
“…This indicated that DSS administration damaged the antioxidative ability, which may subsequently cause the onset of colitis onset. This is consistent with previous reports (26,27). In the present study, UA treatment for 7 days significantly improved the increased MDA content and decreased SOD activity in the colon tissues.…”
Section: Discussionsupporting
confidence: 82%
“…This indicated that DSS administration damaged the antioxidative ability, which may subsequently cause the onset of colitis onset. This is consistent with previous reports (26,27). In the present study, UA treatment for 7 days significantly improved the increased MDA content and decreased SOD activity in the colon tissues.…”
Section: Discussionsupporting
confidence: 82%
“…Despite the intimate connection between liver and colon, the oxidative and inflammatory alterations found in our model of mild colitis (2% of DSS, v/v, for 5 days) could have been insufficient to cause liver damage, unlike the results of Trivedi and Jena [57] and Farombi et al [58]. However, when histological (Figure 6(a)), serological (Table 2), oxidative (Figure 7), and inflammatory (Figure 8) parameters were evaluated, hepatic damage in the LA + NAC group was identified.…”
Section: Discussioncontrasting
confidence: 68%
“…Therefore, favorable regulation of these inflammatory mediators could provide a feasible therapeutic strategy for the treatment of UC. A previous study has shown that protocatechuic acid could adjust inflammatory cytokines as well as inhibited COX-2 and iNOS to alleviate UC (Farombi et al, 2016). In this study, treatment with BGF effectively inhibited the uncontrolled release of TNF-a, IL-6, IL-1b, and IFN-g, and increased the level of IL-10 as compared with the UC mice (all p < 0.01).…”
Section: Discussionsupporting
confidence: 62%